2013
DOI: 10.7314/apjcp.2013.14.8.4647
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BreastLight as a Tool for Early Detection of Breast Lesions among Females Attending National Cancer Institute, Cairo University

Abstract: Background: Breast illumination was suggested as a simple method for breast cancer screening. BreastLight is a simple apparatus for this purpose. Objective: To evaluate the diagnostic performance of BreastLight as a screening tool of breast cancer in comparison to mammography and histopathology. Materials and Methods: This hospital-based cross sectional study was conducted in the mammography unit of the radiodiagnosis department at National Cancer Institute, Cairo University. All participants were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
(12 reference statements)
1
17
1
Order By: Relevance
“…The mean age of patients with MDE was 33.58±8.81 years in the present study, consistent with another report ( 17 ). However, the mean age of patients with breast cancer was 44.97±11.04 years, inconsistent with Jemal et al ( 18 ) who demonstrated that breast cancer frequently occurred in patients at the age of 50–69 years; however, Labib et al ( 19 ) demonstrated that the mean age was 46.3±12.4 years, similar to the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…The mean age of patients with MDE was 33.58±8.81 years in the present study, consistent with another report ( 17 ). However, the mean age of patients with breast cancer was 44.97±11.04 years, inconsistent with Jemal et al ( 18 ) who demonstrated that breast cancer frequently occurred in patients at the age of 50–69 years; however, Labib et al ( 19 ) demonstrated that the mean age was 46.3±12.4 years, similar to the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…[3] Evaluation of 310 patients between 2012 and 2013 in Cairo reported much better results with the breast light, with sensitivity, specificity, positive predictive value, negative predictive value and total accuracy of 93.0%, 73.7%, 91.4%, 77.8% and 88.2%, respectively. [4] Shiryazdi et al [5] concluded in another Iranian study that the performance of the breast light in detection of lesions ≤1 cm assessed by CBE, mammography and sonography was 4.4%, 7.7% and 12.5%, respectively, and for masses >4 cm, 65%, 100% and 57.1%. [5] The performance of the breast light in detection was significantly increased with larger masses (p<0.001), which once again challenges the notion that this device can be used as a screening tool equivalent to mammography.…”
Section: Breast Lightmentioning
confidence: 99%
“…Sensitivity of 93%, and specificity of 73.7% were also reported by authors. 35 In this study, image processing was conducted by a MATLAB-based software similar to that reported by Godavarty et al 2 For improving the detectability of images. In addition to MATLAB software, NIR images for major and minor vessels were processed by ImageJ software too, and the result was similar (no significant difference was observed).…”
Section: Discussionmentioning
confidence: 99%